The effect of using the learning cycle method on the achievement and retention of mathematics among the fourth scientific grade students. (Journal of the College of Basic Education, 2022)
Our society lives in a rapidly changing world surrounded by local and global challenges, perhaps the most important of whichThe explosion of knowledge and technological development and the expansion of the dimensions of human civilization and its development, which is the result ofMan’s use of his mind. These abilities are present in all individuals in varying proportions, but they need to be awakened.Training and preparing individuals who are capable of diversified and new production, so that the curriculum embodies its content and methods.And his methods, teaching methods must receive the most attention by relying on strategies modern.